Review of bioinspired aquatic jumping robots - Tao Zhang; Jiawei Dong; Qianqian Chen; Xiongqian Wu; Shuqi Wang; Yisheng Guan (Biomimetic Intelligence and Robotics)
In natural, aquatic and amphibians creatures have evolved exceptional impulsive-based, momentum-based, and mixed water–air cross domain locomotion capabilities through long-term natural selection, providing significant reference and inspiration for the design of aquatic jumping robots. In recent years, inspired by nature and biology, researchers have turned to jumping as a potential mode of locomotion for aquatic robots, aiming to improve their adaptability across water–air environment. However, the performance of these robots remains significantly limited, far from meeting practical application requirements, due to issues like inadequate propulsion efficiency, high structural resistance, and excessive weight. This paper summarizes the key features of bioinspired aquatic jumping robots, including their bioinspired structural designs, jumping mechanisms, and actuators, while evaluating their jumping performance. Finally, the current challenges are analyzed, and future prospects for development are discussed.